Digitising Libyan heritage: inscriptions and toponomy. (November 2019) - Abdelhamed, Muna H. Haroun; Roueché, Charlotte
Abstract: The new digital technologies have become an effective tool for researchers in different fields. Historians and archaeologists who are studying Greek and Roman Libya have benefited from technical developments in presenting different kinds of data, particularly relating to the epigraphy and toponymy of Libya. They have recently published several resources, and are working on more. This study presents the story of how scholars have collected a variety of Libyan heritage materials and published them online; the account makes it clear that these digital projects are the result of extensive and ongoing collaboration between researchers from different countries, including Libya. They have worked together, and are still working to produce valuable online corpora of inscriptions alongside the Heritage Gazetteer of Libya which records names used at different times, and in a variety of languages, of heritage sites. We also discuss plans for further improving the accessibility of these materials, and encouraging their wider use. Abstract : أصبحت التقنيات الرقمية الحديثة أداة فعالة للباحثين في مجالات مختلفة، وقد استفاد المؤرخون والآثاريون، المهتمون بتاريخ ليبيا وآثارها في الفترتين الإغريقية والرومانية، من التطورات التقنية لتقديم بيانات (data) مختلفة وخاصة تلك المتعلقة بالنقوش ودراسة مسميات المواقع الأثرية بليبيا. قام هؤلاء حديثاً بنشر مصادر متعددة، معضمها لنقوش، ولا يزال العمل مستمر على أعمال أخرى. توضح هذه الدراسة الكيفية التي تمكن خلالها الباحثون من جمع مواد متنوعة من التراث الليبي، ثم نشرها لتكون متاحة للجميع على الشبكة العنكبوتية (الإنترنت). تُبين هذه الورقة بشكل جلي أن هذه المشاريع الرقمية جاءت نتيجة تعاون مكثف ودؤوب بين باحثين من بلدان عِدَّة بما فيها ليبيا. حيث عملوا معاً ولا يزالوا مستمرين في تقديم مجموعة قيمة للنقوش الإغريقية واللاتينية، بالإضافة إلى فهرس جغرافي يسجل اسماء لمواقع أثرية اُستخدمت في حقب مختلفة وسُميت بلغات متعددة. كما ناقشت هذه الورقة خططاً من شأنها تطويرإمكانية الوصول لهذه المواد التراثية وتشجيع استخدامها على نطاق موسع .